Detection and quantification of Colletotrichum abscissum from leaves of budwood increase block and citrus nursery plants by real time PCR - Vargas Munõz, Vanessa Nathalia (2018)
Brazil is the largest citrus producer in the world and has a large global citrus market share. However, several diseases affect the crop, being postbloom fruit drop (PFD) one of them. PFD has gained importance in São Paulo State for the displacement of citrus areas to regions with weather conditions more favorable for this disease. The accurate identification of the causal agent of the PFD has been performed and it was renamed as Colletotrichum abscissum. The origin of the initial inoculum is still an enigma for PFD epidemics and the hypotheses that the initial inoculum could be present in propagation material have been discussed but it has never been demonstrated. The objective of this work was to detect and quantify Colletotrichum abscissum from citrus leaves of budwood increase block and citrus nursery plants by qPCR. Four commercial citrus farms from São Paulo State, Brazil with budwood increase block and citrus nursery plants of Pera and Valencia sweet orange varieties were used for this work. C. abscissum was detected in budwood increase block and in nursery plant in both varieties (Valencia and Pera) at the four farms sampled. Out of 122 budwood increase block samples, 89 (73%) were positive for C. absicissum. From nursery plants, out of 175 samples, 129 (73%) were detected with the pathogen. The majority of the positive samples of budwood increase blocks and nursery plants contained 10 to 200 and 10 to 400 conidia of C. absicissum, respectively. With the methods used was not possible to isolate the fungus from vegetative material. This finding suggests a new long distances dispersion type of C. abscissum in the cycle of postbloom fruit drop by propagation material. Confirmation of C. abscissum in budwood increase block and nursery plants would lead to update regulations for the production of certified citrus nursery trees and searching for new control strategies of the pathogen.